(untitled) (Sebha University Conference Proceedings, 2025)
A study was conducted to synthesize segmented copolymers consisting of Siloxane-Alphatic-Aromatic copolymer segments using a three-step polymerization reaction. The chemical composition of the copolymers was analyzed using Gradient Elution Chromatography GEC and Nuclear Magnetic Resonance NMR spectroscopy after Soxhlet extraction. The study also developed a solid phase extraction method to extract the Siloxane SI, Aliphatic ALE, and Aromatic ARE homopolymers from the copolymers simultaneously. Some samples of the copolymers exhibited complete solubility in chloroform due to their low content of Aliphatic-Aromatic copolymer ARE. The findings provide insights into the synthesis, characterization, and extraction of segmented copolymers.